Covering Islam in Western Media: From Islamic to Islamophobic Discourses - Bouchaib Benzehaf (Journal of English Language Teaching and Linguistics, 2017)
A fundamental role allocated to the media is the shaping of public opinion about topical issues, thus making the act of obtaining accurate and verified information a major challenge. In this context, Said (1997) argues that coverage of Islam by the media has always been lacking in subjectivity, and Arabs/Muslims have at best been obscured and at worst “othered” and demonized rather than revealed by the media. The 9/11 attacks have re-triggered an explosion of media coverage of Islam and Muslims with the terms "Muslim" and "Terrorist" becoming synonymous in many western countries. The attacks have been exploited to cause a social anxiety/panic toward Islam and Muslim cultures leading to Islamophobia which is being further reinforced in Trump’s America. Situated within the framework of Said’s Orientalism, which helps us understand the relationships between the West and the Muslim world and also framed by agenda-setting media theory, which explains how media manipulate public opinion, this paper argues that Islamophobia results from the way the news stories regarding Islam and Muslims are covered. In particular, these stories are media(ated) and thus distorted. The paper borrows tools from critical discourse analysis, particularly global meanings and lexicalization, to analyse selected examples of media(ted) coverage of Islam and Muslim stories from different media sources with the aim of offering a holistic review of the scope and nature of the coverage of Islam and Muslims. In light of the results, we suggest interfaith dialogue and intercultural education as measures that can bring about understanding and tolerance between different religious communities.